The fallacy of the fiscal theory of the price level: One last time - Willem H. Buiter; Anne C. Sibert (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
There have been attempts to resurrect the fiscal theory of the price revel (FTPL). The original FTPL rests on a fundamental compounded fallacy: confusing the intertemporal budget constraint (IBC) of the State, holding with equality and with sovereign bonds priced at their contractual values, with a misspecified equilibrium nominal bond pricing equation, and the 'double use' of this IBC. This generates a number of internal inconsistencies and anomalies. The FTPL is not about endogenous money issuance guaranteeing solvency of the State when public spending and taxes are exogenous. The problem is not about empirical content or the realism of the assumptions, but about flawed internal logic. The issue is not just of academic interest. If fiscal authorities were to take the FTPL seriously, costly policy accidents, including sovereign default and hyperinflation, could result. Interpreting the FTPL as an equilibrium selection mechanism in models with multiple equilibria does not help. Attempts by Sims to extend the FTPL to models with nominal price rigidities fail. The attempted resurrection of the FTPL fails.
Keywords: E31; E40; E50; E58; E62; H62; H63; 330; fiscal theory of the price level; intertemporal budget constraint; equilibrium bond pricing equation; monetary and fiscal policy coordination; equilibrium selection; fiscal dominance